The effect of a hydrophilic bonding primer on the shear bond strength of molar tubes bonded to dry and moisture contaminated porcelain surfaces - Akhoundi, Maryam Ahmad
General objective: The purpose of this in vitro study was to determine the effect of hydrophilic bonding primer on the shear bond strength of orthodontic molar tubes bonded to porcelain.